Finding Exact Solution For Generalized Burgers-Huxley Equation With Constant Coefficients by the modified (G'/G ) expansion method. (Latakia University Journal -Basic Sciences Series, 2018)
The aim of this work is finding exact solutions to generalized Burger's-Huxley equation with constant coefficients, by using the modified (G'/G )-expansion method, Where we get the application of the steps of the modified (G'/G )-expansion method on the statement of nine equations with nine variables .we solve it with aid of symbolic programs as Maple and Mathematica